2020
DOI: 10.3389/fmicb.2020.00212
|View full text |Cite
|
Sign up to set email alerts
|

Comparison on the Growth Variability of Vibrio parahaemolyticus Coupled With Strain Sources and Genotypes Analyses in Simulated Gastric Digestion Fluids

Abstract: Vibrio parahaemolyticus is a food-borne pathogen that causes pathogenic symptoms such as diarrhea and abdominal pain. Currently no studies have shown that either pathogenic and non-pathogenic V. parahaemolyticus possess growth heterogeneity in a human environment, such as in gastric and intestinal fluids. The tlh gene is present in both pathogenic and non-pathogenic V. parahaemolyticus strains, while the tdh and trh genes are only present in pathogenic strains. This study firstly applied simulated human gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…This is in accordance with Koo et al (2000) and Wang et al (2019) as they also found pH levels <4 led to a decrease in cell viability in both V. parahaemolyticus and V. vulnificus . While V. parahaemolyticus did have decreased biofilm cell viability and cell dispersal at acidic (pH = 4) conditions compared to higher pHs, it was still able to tolerate this acidic pH for two hours, which was consistent with results of Wang et al (2019 , 2020) . There was also a decrease in biofilm cell viability and cell dispersal of both species after exposure to SGF, which more closely resembles the gastric liquid composition in the stomach’s environment.…”
Section: Discussionsupporting
confidence: 82%
“…This is in accordance with Koo et al (2000) and Wang et al (2019) as they also found pH levels <4 led to a decrease in cell viability in both V. parahaemolyticus and V. vulnificus . While V. parahaemolyticus did have decreased biofilm cell viability and cell dispersal at acidic (pH = 4) conditions compared to higher pHs, it was still able to tolerate this acidic pH for two hours, which was consistent with results of Wang et al (2019 , 2020) . There was also a decrease in biofilm cell viability and cell dispersal of both species after exposure to SGF, which more closely resembles the gastric liquid composition in the stomach’s environment.…”
Section: Discussionsupporting
confidence: 82%
“…The maximum specific growth rate ( μ max ) and lag time (LT) are considered to be the two most important parameters of microbial dynamics, which can reflect the growth advantages of bacterial strains, fitting, and virulence ( 30 ). Short LT and/or high μ max generally present a positive correlation with virulence of bacterial strains; however, in our work, we have found no such trend (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…V. parahaemolyticus is a foodborne pathogen that is known to form biofilms, which can increase bacterial resistance and contribute to foodborne disease burdens [ 17 , 18 , 19 , 20 ]. There exists V. parahaemolyticus isolates that are 90.5% antibiotic resistant to amikacin [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%